Killing the witches : the horror of Salem, Massachusetts - O'Reilly, Bill; Dugard, Martin (New York : St. Martin's Press, 2023)
"Killing the Witches revisits one of the most frightening and inexplicable episodes in American history: the events of 1692 and 1693 in Salem Village, Massachusetts. What really happened in Salem? Killing the Witches tells the horrifying story of a colonial town's madness, offering the historical context of similar episodes of community mania during that time, and exploring the evidence that emerged in the Salem trials, in contemporary accounts, and in subsequent investigations."--
Includes bibliographical references and index.
Keywords: Witches -- Violence against -- Massachusetts -- Salem -- History -- 17th century; Trials (Witchcraft) -- Massachusetts -- Salem -- History -- 17th century; Salem (Mass.) -- History -- Colonial period, ca. 1600-1775.